PERSEPSI MASYARAKAT TERHADAP KEUNIKAN ALAM DANAU BATUR BALI - Riyawati Ika Dewi (Program Studi Manajemen Lingkungan, 2020)
This study aimed to obtain information about the public perception of the effect of supporting the infrastructure development of the unique nature of Lake Batur Lake Batur, in the district of Kintamani, Bangli regency of Bali Province. This study used survey method with descriptive quantitative approach. Collecting data using the questionnaire technique. The data analysis technique used is the test requirements analysis, simple linear regression analysis with a sample of 20 people (10 women and 10 men). The result is the development of supporting infrastructure implemented in the ecotourism object of Lake Batur in harmony with the natural beauty of Lake Batur. This can be seen from the opinions and perceptions of visitors who say that the uniqueness of Lake Batur nature is maintained and still can be enjoyed from the first until now. According Deputy for Tourism Destination Development and Investment of the Ministry of Tourism, 2016 for tourist visit to Indonesia, there are 3 kinds of products that interest are Natural (nature) 35%, Culture 60% and Man Made 5%. Lake Batur is a product for tourism objects that combine natural products and cultural products. One thing that can not be separated from the existence of Mount Batur is Lake Batur. Lake Batur is located in the District Kitamani, Bangli regency, is the largest lake on the island of Bali. Data on the potential of natural resources in a volcano ecosystem as a whole and comprehensive is important to know as the basis for making sustainable development planning. Keywords: Public perception, uniqueness of nature, Lake Batur